2014
DOI: 10.3390/nu6114895
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Exercise Dependence and Eating Disorders in Young Adults: A Path Analysis of a Conceptual Model

Abstract: The purpose of our study was to study the prevalence of exercise dependence (EXD) among college students and to investigate the role of EXD and gender on exercise behavior and eating disorders. Excessive exercise can become an addiction known as exercise dependence. In our population of 517 college students, 3.3% were at risk for EXD and 8% were at risk for an eating disorder. We used Path analysis the simplest case of Structural Equation Modeling (SEM) to investigate the role of EXD and exercise behavior on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 29 publications
5
26
0
Order By: Relevance
“…The lack of difference in EAT‐26 scores and disordered eating between ND and OT cohort in our sample is supported by other comparative studies that showed no difference in ED risk between nutrition and other health and non‐health degree students. The overall proportion of symptomatic individuals in this research (approximately 13%) is within the range of previously reported in community sample (5–13%) and in university students enrolled in health (9–20%) and non‐health (8–21%) degrees. The relatively wide ranges in the prevalence of ED make it challenging to suggest whether nutrition‐orientated degrees in particular, or health degrees in general, have an effect on eating attitudes.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The lack of difference in EAT‐26 scores and disordered eating between ND and OT cohort in our sample is supported by other comparative studies that showed no difference in ED risk between nutrition and other health and non‐health degree students. The overall proportion of symptomatic individuals in this research (approximately 13%) is within the range of previously reported in community sample (5–13%) and in university students enrolled in health (9–20%) and non‐health (8–21%) degrees. The relatively wide ranges in the prevalence of ED make it challenging to suggest whether nutrition‐orientated degrees in particular, or health degrees in general, have an effect on eating attitudes.…”
Section: Discussionsupporting
confidence: 85%
“…Another concerning find of this study is a high proportion of participants from both cohorts that experienced eating binges and the smaller numbers that reported using laxatives, diet pills, diuretics and vomiting after meals. These disordered eating behaviours have been previously reported in university students enrolled in nutrition and non‐nutrition degrees . For example, one study on body and weight attitudes and behaviours of dietetic students found that out of 74% of participants who attempted to lose weight, up to 15% thought laxatives were and up to 11% found that vomiting after meals was helpful in weight loss .…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…(1) Eating disorders also affect physical and nutritional health, psychological functioning and if untreated, they can be fatal. (2) Earlier studies have shown that eating disorders have the highest mortality rate of any mental illness. (3) According to DSM-5, the types of eating disorders are Anorexia Nervosa, Bulimia Nervosa, Binge Eating Disorder, Pica, Rumination Disorder, Avoidant/Restrictive Food Intake Disorder (ARFID), Other Specified Feeding or Eating Disorder (OSFED).…”
Section: Introductionmentioning
confidence: 99%